Evaluation of a New Wireless Temperature Remote Interrogation System (TEMPRIS) to Measure Product Temperature During Freeze Drying - Schneid, Stefan (Springer US, 2008)
The purpose of this research was to evaluate a new wireless and battery-free sensor technology for invasive product temperature measurement during freeze-drying. Product temperature is the most critical process parameter in a freeze-drying process, in particular during primary drying. The product temperature over time profile and a precise detection of the endpoint of ice sublimation is crucial for comparison of freeze-drying cycles. Traditionally, thermocouples are used in laboratory scale units whereas resistance thermal detectors are applied in production scale freeze-dryers to evaluate temperature profiles. However, both techniques show demerits with regard to temperature comparability and biased measurements relative to vials without sensors. A new generation of wireless temperature sensors (Temperature Remote Interrogation System, TEMPRIS) were used in this study to investigate for the first time their value when applied to freeze-drying processes. Measurement accuracy, capability of accurate endpoint detection and effect of positioning were delineated by using product runs with sucrose, mannitol and trehalose. Data were compared to measurements with 36-gauge thermocouples as well as to non-invasive temperature measurement from Manometric Temperature Measurements. The results show that the TEMPRIS temperature profiles were in excellent agreement to thermocouple data when sensors were placed center bottom in a vial. In addition, TEMPRIS sensors revealed more reliable temperature profiles and endpoint indications relative to thermocouple data when vials in edge position were monitored. The results of this study suggest that TEMPRIS may become a valuable tool for cycle development, scale-up and routine manufacturing in the future.